LISA FAKTOR-FAKTOR YANG MEMPENGARUHI PENGETAHUAN DAN SIKAP PERAWAT DALAM PENCEGAHAN DAN PENGENDALIAN INFEKSI COVID-19 - Wahyuningsih, Indah Sri (Jurnal Perawat Indonesia, 2021)
Determinant Factors of Knowledge and Attitude Nurses’ to Prevent and Control COVID-19 Infection. The main principles of nurse during caring patients with COVID-19 are knowing prevent and control of COVID-19 infection. The increase of knowledge and attitudes are not only determine of age maturity but also other factors. This study aimed to determine factors determinant the knowledge and attitude of nurses in preventing and controlling COVID-19 infection. The present study employed quantitative with analytic observational method with cross-sectional design. The study was conducted in three hospitals at Semarang from May to June 2020 with a sample size of 60 respondents. The inclusion criteria are nurses who work in the emergency unit, the COVID-19 isolation room, ICU, permanent nurses and are not on duty. Meanwhile, the exclusion criteria are nurses who have work experience of less than two years and interns. Each independent variable is evaluated using logistic regression analysis to determine the most influential variable. The results of this study analyzed with wald test that indicate that the variables of training and education have an determine on knowledge with an accuracy level of 68.33%, while the variables of the age group, work unit and education have an effect on nurses' attitudes with an accuracy level of 80.00%. The results of this study indicate that the variables of the age group, work unit and education have the most influence on nurses 'attitudes in infection prevention and control, while training and education variables have the most influence on nurses' knowledge in preventing and controlling COVID-19 infection.